2021
DOI: 10.1177/23197145211028041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Analytics in Supply Chain Management from Industry and Academic Perspective

Abstract: Information and communication technology (ICT) has been the backbone of businesses for some time now. ICT adoption has rendered data availability in vertically connected organizations. In recent times, the rise of analytics has paved the way to rethink the structure and working of vertically connected firms within a supply chain. Big data analytics (BDA) for instance, has become a prominent tool to analyse unstructured data. This study explores the application and benefit of various types of analytics such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Extant literature suggests that BT and Internet of Things (IoT) and big data analytics (BDA) can bridge the inefficiencies in the agri-food supply chain (Kumar et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature suggests that BT and Internet of Things (IoT) and big data analytics (BDA) can bridge the inefficiencies in the agri-food supply chain (Kumar et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in this paper, we focus on the pricing and operations aspects of SaaS. 2010 (Kiddoo et al, 2019;Kumar, 2021). Rooted in the Internet and cloud computing, SaaS may aggregate diverse data sources to create "data lakes" for business analytics.…”
Section: The Frameworkmentioning
confidence: 99%
“…Diverse research methodologies can be found in SaaS research, such as queuing (e.g., Li & Kumar, 2018; Saha et al., 2021), econometrics (e.g., Chu & Manchanda, 2016), and mixed methodologies (e.g., Mookerjee et al., 2017). These methodologies facilitated the Federal Communications Commission's successful auction of wireless spectrum since 2010 (Kiddoo et al., 2019; Kumar, 2021). Rooted in the Internet and cloud computing, SaaS may aggregate diverse data sources to create “data lakes” for business analytics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data-driven decisions could also help them make a sustainable supply chain. Recently, Kumar et al (2021Kumar et al ( , 2022 have investigated various types of analytics in supply chains, and those applications are extended using the theme created by topic modeling. Table 10 shows how analytics could solve various supply chain issues.…”
Section: Social Media Information In Supply Chain (Theme 5)mentioning
confidence: 99%